Response to “Comment on ‘Static correlations functions and domain walls in glass-forming liquids: The case of a sandwich geometry”’ [J. Chem. Phys. 144, 227101 (2016)] - Gradenigo, Giacomo (2016)
The point-to-set correlation function has proved to be a very valuable tool to probe structural correlations in disordered systems, but more than that, its detailed behavior has been used to try to draw information on the mechanisms leading to glassy behavior in supercooled liquids. For this reason it is of primary importance to discern which of those details are peculiar to glassy systems, and which are general features of confinement. Thus the concerns raised in Ref. 1 definitely need to meet an answer. The Comment proposes an alternative analysis of the numerical data presented in Ref. 2, according to which the behaviour of the point-to-set correlation function can be interpreted as a linear superposition of boundary effects, rather than the effect of non-trivial thermodynamics. We believe this alternative explanation is not compelling.